2008
DOI: 10.1002/jmri.21499
|View full text |Cite
|
Sign up to set email alerts
|

Double‐reference cross‐correlation algorithm for separation of the arteries and veins from 3D MRA time series

Abstract: Purpose: To present a novel postprocessing technique for artery/vein separation and background suppression from contrast-enhanced time-resolved magnetic resonance angiography datasets in order to improve the diagnosis of vessel pathologies and arteriovenous fistulas. Materials and Methods:Ten normal, two pathologic datasets of the brain, and one hand angiography dataset were postprocessed. Cross-correlation maps between the signal time course of every voxel in the dataset and selected arterial and venous refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…One study used a cross-correlation analysis (CCA) of perfusion data sets for suppression of central pulmonary vessels [47]. CCA has previously been used to improve the SNR and arteriovenous separation in time-resolved MR angiography [48, 49]. It was shown that it is feasible to identify vessels with a similar signal-intensity time curve as a reference vessel using CCA.…”
Section: Contrast-enhanced Mr Perfusionmentioning
confidence: 99%
“…One study used a cross-correlation analysis (CCA) of perfusion data sets for suppression of central pulmonary vessels [47]. CCA has previously been used to improve the SNR and arteriovenous separation in time-resolved MR angiography [48, 49]. It was shown that it is feasible to identify vessels with a similar signal-intensity time curve as a reference vessel using CCA.…”
Section: Contrast-enhanced Mr Perfusionmentioning
confidence: 99%
“…For the calculation of maximum intensity projection (MIP), CCA improves the signal-to-noise ratio compared with simple image subtraction [16]. A novel double-reference cross-correlation technique enables the correct separation of arteries and veins, even in the presence of bolus dispersion, where subtraction and standard CCA have difficulties with discrimination [17].…”
Section: Ccamentioning
confidence: 99%
“…Cross-correlation analysis (CCA) has previously been used to improve the signal-to-noise ratio and arteriovenous separation in time-resolved MR angiography [16,17]. It has been shown that it is feasible to identify vessels with a similar signal-intensity time-curve as a reference vessel using CCA.…”
Section: Introductionmentioning
confidence: 99%